Stress‐induced escalation of alcohol self‐administration, anxiety‐like behavior, and elevated amygdala Avp expression in a susceptible subpopulation of rats. (9th February 2021) - Barchiesi, Riccardo; Chanthongdee, Kanat; Domi, Esi; Gobbo, Francesco; Coppola, Andrea; Asratian, Anna; Toivainen, Sanne; Holm, Lovisa; Augier, Gaelle; Xu, Li; Augier, Eric; Heilig, Markus; et al.
Abstract: Comorbidity between alcohol use and anxiety disorders is associated with more severe symptoms and poorer treatment outcomes than either of the conditions alone. There is a well‐known link between stress and the development of these disorders, with post‐traumatic stress disorder as a prototypic example. Post‐traumatic stress disorder can arise as a consequence of experiencing traumatic events firsthand and also after witnessing them. Here, we used a model of social defeat and witness stress in rats, to study shared mechanisms of stress‐induced anxiety‐like behavior and escalated alcohol self‐administration. Similar to what is observed clinically, we found considerable individual differences in susceptibility and resilience to the stress. Both among defeated and witness rats, we found a subpopulation in which exposure was followed by emergence of increased anxiety‐like behavior and escalation of alcohol self‐administration. We then profiled gene expression in tissue from the amygdala, a key brain region in the regulation of stress, alcohol use, and anxiety disorders. When comparing "comorbid" and resilient socially defeated rats, we identified a strong upregulation of vasopressin and oxytocin, and this correlated positively with the magnitude of the alcohol self‐administration and anxiety‐like behavior. A similar trend was observed in comorbid witness rats. Together, our findings provide novel insights into molecular mechanisms underpinning the comorbidity of escalated alcohol self‐administration and anxiety‐like behavior. Abstract : Comorbid alcohol use disorder and anxiety disorders are associated with more severe symptoms and poorer treatment outcomes compared to either condition alone. Similar to the clinical situation, social defeat and witness stress induce co‐occuring anxiety‐like behaviors and escalation of alcohol self‐administration in a subpopulation of rats, supporting a translational validity of our animal model. We found a positive correlation between Avp expression in the amygdala and the magnitude of stress‐induced comorbid escalated alcohol intake and anxiety‐like characteristics.